Most British Surgeons Would Consider Using a Tissue-Engineered Anterior Cruciate Ligament: A Questionnaire Study - Sarah Rathbone; Nicola Maffulli; Sarah H. Cartmell (Stem Cells International)
Donor site morbidity, poor graft site integration, and incorrect mechanical performance are all common problems associated with autografts for anterior cruciate ligament (ACL) reconstructions. A tissue-engineered (TE) ligament has the potential to overcome these problems. We produced an online questionnaire relating to tissue engineering of the ACL to obtain input from practising clinicians who currently manage these injuries. 300 British orthopaedic surgeons specialising in knee surgery and soft tissue injury were invited to participate. 86% of surgeons would consider using a TE ACL if it were an option, provided that it showed biological and mechanical success, if it significantly improved the patient satisfaction (63%) or shortened surgical time (62%). 76% felt that using a TE ACL would be more appropriate than a patellar tendon, hamstring, or quadriceps autograft. Overall, most surgeons would be prepared to use a TE ACL if it were an improvement over the current techniques.